Characterization of resistive heating and thermoelectric behavior of discontinuous carbon fiber-epoxy composites. (1st April 2016) - Kim, Myungsoo; Sung, Dae Han; Kong, Kyungil; Kim, Nari; Kim, Byeong-Joo; Park, Hyung Wook; Park, Young-Bin; Jung, Mooyoung; Lee, Sang Hwan; Kim, Su Gi
Abstract: The resistive heating and thermoelectric characteristics of discontinuous carbon fiber-epoxy composites are explored experimentally and numerically. Composite samples with different carbon fiber concentrations (1, 3, and 5 wt.%) were manufactured using sonication and cast molding. DC current was applied, and the temperature distributions on the surfaces of the samples were assessed visually and quantitatively using an infrared camera. The resistive heating mechanism was investigated in conjunction with applied voltage and carbon fiber loading. Experimental results show that resistive heating efficiency increased proportionately with applied voltage and carbon fiber content, and this was confirmed by numerical simulations of fiber contacts at various fiber volume fractions using representative volume elements. In parallel, the thermoelectric behavior of composites was characterized using a specially designed and fabricated test setup. The discontinuous carbon fiber-epoxy composites showed p-type thermoelectric behavior, and the generated voltage and Seebeck coefficient increased with increasing applied temperature and temperature difference.